Pengaruh pemberian ekstrak jamur merang (volvariella volvacea) terhadap kadar kolesterol total, enzim lppla2 dan mda darah - Damayanty, Amelia Eka; Suromo, Lisyani B.; Kisdjamiatun, RA (Department of Nutrition Science, Faculty of Medicine, Universitas Diponegoro, 2015)
Background: Consumption of high-fat diet (HFD) is increasing blood total cholesterol, LpPLA2 enzyme and MDA level which is a cause of atherosclerosis that should be controlled by antioxidants. Paddy straw mushroom (Volvariella v.) extract has an antioxidant compounds. This research proves the effect of Volvariella v. extract on blood total cholesterol (TC), LpPLA2 enzyme and MDA level, and proves correlation between TC with LpPLA2 enzyme and MDA level.Methods: A randomized post test only control group design to twenty four of 8-10 weeks old male Rattus novergicus Wistar strain with 180-200 gram were divided into four group; K1 with standard diet, K2 with HFD, each X1 and X2 with HFD+Volvariella v. extract 500 mg/kg.bwt/day and 1000 mg/kg.bwt/day. All treatments for 56 days. TC levels assesed by enzymatic colorimetric test method, LpPLA2 enzyme with ELISA method and MDA with TBARs method. Data were analyzed by one way Anova, LSD post hoc and Pearson’s correlation.Results: TC mean of K1 (91,28±1,55 mg/dL), K2 (181,96±4,19 mg/dL), X1 (122,94±2,75 mg/dL) and X2 (105,86±2,25 mg/dL); p=0,001. Enzyme LpPLA2 mean of K1 (2,65±3,19 ng/mL), K2 (1,29±1,35 ng/mL), X1 (3,92±2,18 ng/mL), X2 (2,05±3,29 ng/mL); p=0,385 and blood MDA mean of K1 (1,17±0,12 nmol/mL), K2 (5,75±0,21 nmol/mL), X1 (2,96±0,91 nmol/mL) and X2 (1,77±0,92 nmol/mL); p=0,001. Correlation between TC and LpPLA2 enzyme was shown by X1 group (p=0,042; r = - 0,827).Conclusion:Volvariella v. extract decreased blood total cholesterol and MDA level significantly, did not significant to LpPLA2 enzyme. There wss a correlation between TC and LpPLA2 enzyme but was not to TC and blood MDA.